Mathematical Modeling Of Energy Consumption And Separation Efficiency Of Multicyclones For Air Purification (Eurasian Journal of Engineering and Technology, 2025)
Multicyclones—compact arrays of small-diameter cyclone cells—remain the work-horse technology for removing coarse dust from industrial exhaust streams thanks to their low capital cost and mechanical robustness. Their main drawbacks are the pressure drop that drives fan energy demand and the inherent trade-off between energy use and collection efficiency. This paper develops an integrated mathematical model that couples (i) gasdynamics-based correlations for pressure drop, (ii) Barth’s static-particle theory for grade efficiency, and (iii) a fan-power model to quantify specific energy consumption (SEC) per tonne of dust captured. A parametric simulation covering volumetric flow rates 0.05 – 0.8 m³ s⁻¹ per cell, cyclone diameters 0.1 – 0.3 m, and dust particle diameters 1 – 20 µm is implemented in Python/MATLAB. Results (Figure 1) show ΔP rising quadratically with superficial velocity, while the predicted collection curve (Figure 2) exhibits a typical Sshape with 50 % cut size d₅₀ ≈ 5 µm. The combined model reveals a sweet-spot operating window (5 – 8 m s⁻¹) where SEC is minimized without compromising ≥ 80 % overall efficiency. The framework provides a fast tool for optimising multicyclone banks in retrofits or green-field designs